혁명의 시간 속 예언의 문학: 윌리엄 블레이크의 『미국: 예언』 - 유선무 (안과밖:영미문학연구, 2018)
While it is common to find the strong thematic and stylistic resonance of the words “prophet” and “prophecy” in William Blake's works, he has often been considered a prophet of a mythology that he created. Working against this reading, this paper attempts to place Blake’s prophetic writings in the historical context of the last decade of the eighteenth century, when numerous prophecies proliferated in a reaction to the political upheaval in France. For Blake, prophecy is not a form of prediction but it, instead, involves a more ambivalent relationship to history and time. It is not only directed to the future but to the present to be changed and even to the past to be claimed. Applying Walter Benjamin’s concept of history and time to the reading of America: a Prophecy, this paper reads the poem as an example of the complex temporal dynamics working within the prophetic mode. While describing the American Revolution that occurred more than 15 years ago, America: a Prophecy makes an urgent political call oriented to the present England, where Pitt’s government declared a war against the fledgling French republic. America: a Prophecy makes a claim on the oppressed past of Gordon Riot not as a failed but as an unfulfilled revolution-to-come and tries to blast it out of the continuity and linearity of history. While the revolutionary potential was never actualized in England unlike what America: a Prophecy had prophecized, the disruption of time continuum around which the poem builds the idea of revolution is still applicable to the issues in our own time.
Keywords: William Blake; America: a Prophecy; revolution; prophecy; now-time; disruption of linear time